O-EGS07 Early initiation of biochemical venous thromboembolism prophylaxis following traumatic spleen injury is safe and effectively reduce VTE events. (16th December 2021) - Rizkallah, Georges; Lee, Sheah Lin; Mahmoud, Adel; Handa, Ishada; Long, Joe; Massella, Virginia; Ngan, Franko Shing Fun; Rahman, Atiqur; Johns, Jonathan; Modi, Sachin; Elberm, Hassan
Abstract: Background: The standard of care for managing patients with traumatic splenic injuries (TSI) has become non operative management (NOM) 1, 3, 4, but the safe window initiating chemical venous thromboembolism (VTE) prophylaxis, heparin or low molecular weight heparin (LMWH), is not well established 2 . Within the first 48h from injury, hyper-coagulation state occurs which put trauma patients at risk of developing deep vein thrombosis(DVT), pulmonary embolism (PE) and lead to an increase rate in mortality 5, 6 . This study examines the safety and timing initiating VTE prophylaxis post splenic injury. Methods: Patients with TSI were identified from prospectively maintained Trauma Audit and Research Network (TARN) database from 2015-2020 in a single tertiary trauma centre. Clinical and radio-logical information were collected retrospectively. TSI were graded using American Association for the Surgery of Trauma (AAST) splenic injury scale. Chemical venous thromboprophylaxis initiation were categorised as not given, <48h and >48h following the injury. Results: In total 102 patient were included out of 136 patients identified with TSI. 34 patients were excluded for lack of electronic data, palliative decision or fatal condition on arrival. 12 patients out of 102 required operative management (OM) and 90 patients NOM. VTE prophylaxis was not given for 31 (30.4%). Medical reasons for this include severe brain injury and early discharge before 48 hours. VTE prophylaxis was initiated for 37 (36.3%) patients within 48 hours, and for 34 patients (33.3%) after 48 hours of admission. Seven patients developed thromboembolic events, majority of which (6/7) received VTE prophylaxis after 48 hours. Importantly, none of the patients who received VTE prophylaxis had rebleeding. Conclusions: This study showed that early initiation of chemical VTE prophylaxis (<48h) is safe, resulted in lower incidence of DVTs/PEs without increasing the risk of bleeding. Results from this study supports recommendation from other studies 1 to initiate chemical VTE prophylaxis after TSI as early as 24h post injury with no other contra-indications